LEGAL ISSUES OF TRANSFER OF LAND RIGHTS THROUGH SALE AND PURCHASE THAT DOES NOT ACCORD TO THE PROCEDURE FOR MAKING A DEED OF SALE AND PURCHASE (Study of Supreme Court Decision Number 1196 K/Pdt/2020) - Muhammad Arfananda Ghifari; Solikhah; Burhanudin Harahap (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study discusses the legal issues of land transfer rights through sale and purchase that do not comply with the procedures for making a Deed of Sale and Purchase (AJB) as reflected in Supreme Court Decision Number 1196 K/Pdt/2020. This problem arises because the making of the AJB is not based on the actual wishes of the parties. This study aims to analyze the procedures for making AJB in the decision and the legal consequences that arise for deeds and transfers of land rights based on AJBs that are made not in accordance with procedures. The research method used is normative legal research with a statute approach and a case approach , through an analysis of Supreme Court Decision Number 1196 K/Pdt/2020 which has permanent legal force. The results of the study indicate that the making of AJBs that do not comply with procedures causes the AJB and other related deeds to be declared invalid and have no legal force, so they cannot be used as a basis for transferring land rights. As a result, the Certificate of Ownership issued based on the deed is declared legally flawed and null and void, and creates an administrative obligation for the PPAT holding the protocol to make adjustments and complete the protocol administration in accordance with the provisions of laws and regulations.